ISOLASI DAN IDENTIFIKASI BAKTERI RESISTEN HERBISIDA GLIFOSAT DAN PARAQUAT DARI RIZOSFER TANAMAN PADI - (ISOLATION AND IDENTIFICATION OF RESISTANT BACTERIA TO GLYPHOSATE AND PARAQUAT HERBICIDE FROM RHIZOSPHERE OF RICE PLANTS) - Widowati, Tiwit; Ginting, Rohani Cinta Badia; Widyastuti, Utut; Nugraha, Asep; Ardiwinata, Ardiwinata (Biopropal Industri, 2017)
Glyphosate and paraquat are broad-spectrum herbicides that commonly used in rice fields to control weeds. This study aims to isolate and identificate bacteria from rhizosphere of rice plants which resistant to glyphosate and paraquat herbicides. Thirty bacterial isolates were isolated from rhizosphere of rice plants and screened for their resistance of glyphosate and paraquat herbicides. One isolate was resistant to 4,000 ppm of glyphosate and 1,600 ppm of paraquat. Based on Biolog omniLog identification system, isolate 4.2 was identified as Ensifer meliloti.Keywords: bacteria, herbicide, resistant, rhizosphereÂ Â ABSTRAKGlifosat dan paraquat adalah herbisida berspektrum luas yang biasanya digunakan untuk mengendalikan gulma. Penelitian ini bertujuan untuk mengisolasi dan mengidentifikasi bakteri dari rizosfer padi sawah yang resisten terhadap herbisida glifosat dan paraquat. Tiga puluh isolat bakteri telah diisolasi dari rizosfer padi sawah dan diseleksi resistensinya terhadap herbisida glifosat dan paraquat. Terdapat satu isolat yang resisten terhadap 4.000 ppm glifosat dan 1.600 ppm paraquat. Berdasarkan sistem identifikasi Biolog omniLog, isolat 4,2 merupakan Ensifer meliloti.Kata kunci: bakteri, herbisida, resisten, rizosfer